Cytological Study of Thyroid Lesions by Fine-Needle Aspiration Cytology (Medical Forum Monthly, 2024)
Objective: The present study assessed the cytological and morphological features of thyroid swellings by FNA cytology (FNAC) at a tertiary care hospital of Sindh.Study Design:Place and Duration of Study: This study was conducted at the Department of Surgery and Pathology, Indus Medical College Hospital from January 2016 to Dec 2017.Materials and Methods: A sample of 90 cases of thyroid enlargement was selected according to inclusion and exclusion criteria. Demographic characteristics were noted by clinical history. FNAC was performed by senior surgeon and cytological examination by a senior pathologist. Data was analyzed on SPSS 22.0 at 95% confidence interval (p≤0.ior5).Results: Mean± SD age was noted as 43.56±19.6 years.Of 90 cases, male and female were 33 (36.6%) 57 (63.3%) respectively (p=0.0001). Of 90 cases, the non-neoplastic, neoplastic and indeterminate lesions were noted in 69 (76.6%), 15 (16.6%) and 6(6.6%)respectivelyConclusion: FNAC is a cost effective, uncomplicated and safe diagnostic procedure which may be used for the pre-operative screening of thyroid diseases in poor countries like Pakistan.